2007
DOI: 10.1016/j.jempfin.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Are there Monday effects in stock returns: A stochastic dominance approach

Abstract: We provide a test of the Monday e¤ect in daily stock index returns. Unlike previous studies we de…ne the Monday e¤ect based on the stochastic dominance criterion. This is a stronger criterion than those based on comparing means used in previous work and has a well de…ned economic meaning. We apply our test to a number of stock indexes including large caps and small caps as well as UK and Japanese indexes. We …nd strong evidence of a Monday e¤ect in many cases under this stronger criterion. The e¤ect has revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 37 publications
0
54
0
8
Order By: Relevance
“…The failure to trade over the weekend is expected to make these small traders to close their uncertain positions on Fridays and restore new short positions on Mondays, generating stock prices to grow on Fridays and drop on Mondays. A trend of researchers including Syed and Sadorsky (2006), Cho et al (2007) and Lim et al (2010) provide a reconfirmation of the weekend effect. However, others such as Brusa et al (2003) and Apolinario et al (2006) ignore it.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The failure to trade over the weekend is expected to make these small traders to close their uncertain positions on Fridays and restore new short positions on Mondays, generating stock prices to grow on Fridays and drop on Mondays. A trend of researchers including Syed and Sadorsky (2006), Cho et al (2007) and Lim et al (2010) provide a reconfirmation of the weekend effect. However, others such as Brusa et al (2003) and Apolinario et al (2006) ignore it.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The actual empirical specification we used is rather more flexible, allowing not only for contemporaneous sensitivity but also for a dynamic relationship between R t and RW t where lagged values of order one of the latter will be included in order to capture time lags between Asian and rest of the world markets. We also allow for the ''weekend effect'' or ''Monday effect'' (inter allia: Cho et al 2007;French, 1980;Schwert, 1990a). Since this may bias the regression results dummy variables D i , i=1,..,4, are included in the estimations.…”
Section: Methodsmentioning
confidence: 99%
“…The indings of many studies were consistent with the Monday effect and others have provided the support to the market ef iciency instead of the Monday effect. There are number of studies which have supported the Monday effect in the stock markets (Alt et al, 2011;Cho et al, 2007;Jaffe et al, 1989). However, other studies support the ef icient market hypothesis and are not in line with the Monday effect (Bhana, 1985;Diaconasu et al, 2012;Mehdian and Perry, 2001;Wang et al, 1997).…”
Section: Monday Effectmentioning
confidence: 99%
“…Research studies have documented many anomalous evidences regarding the stock market ef iciency such as January effect (Seyhun, 1993), day of the week effect (Wingender and Groff, 1989), Monday effect (Cho et al, 2007;Jaffe and Wester ield, 1985b), and wandering weekend effect (Doyle and Chen, 2009). Recently, studies have found the irrational behaviour of security prices during the Islamic calendar months such as Ramadan effect (Białkowski et al, 2012).…”
Section: Background Of the Studymentioning
confidence: 99%